Hubungan Waktu Tunggu terhadap Tingkat Kepuasan Pasien di Instalasi Gawat Darurat RSI NU Demak (Maternal & Neonatal Health Journal, 2026)
Emergency Department (ED) services play a crucial role in hospital care quality. Prolonged waiting times may reduce patient satisfaction. This study aimed to determine the relationship between waiting time (independent variable) and patient satisfaction (dependent variable) in the Emergency Department of RSI NU Demak. This study used a cross-sectional design with 85 respondents selected using purposive sampling. Data collection was conducted through direct observation of waiting times and a patient satisfaction questionnaire using BEPSS. Data analysis was performed using univariate and bivariate methods (Spearman's rho test). The results showed that the majority of patients experienced a waiting time of more than 8 hours (76.5%) and most had a moderate level of satisfaction (68.2%). Statistical analysis revealed no significant relationship between waiting time and patient satisfaction levels in the Emergency Department of RSI NU Demak (p = 0.463; r = 0.081). The results suggest that despite the waiting time exceeding the ideal standard, patient satisfaction remained high. This may indicate that factors such as staff empathy, effective communication, service comfort, and socio-economic and demographic backgrounds played a role in shaping patients’ satisfaction.